Amazonia: Landscape and Species Evolution 2009
DOI: 10.1002/9781444306408.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic Sedimentary Evolution of the Amazonian Foreland Basin System

Abstract: In this chapter we present a synthesis of the Cenozoic evolution of the Amazonian foreland basin system, based on a review of the estimated ages, lithology and sedimentary structures, palaeontological content, and inferred depositional environments of sedimentary units in the basin. In addition, we have calculated maximum sedimentation rates for the Cenozoic formations of the northern Peruvian foreland basin and integrated these with existing data on sedimentation rates, subsidence analysis, migration of depoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
1
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 59 publications
(143 reference statements)
10
73
1
9
Order By: Relevance
“…These levels can be correlated with those of the Cruzeiro Formation in the upper Yuruá ("red beds" at the Peru/Brazil border; Oppenheim, 1937). The inferred time span also coincides with that documented by the NPFB for the Pozo Fm using low-temperature thermochronology (Hermoza et al, 2005;Roddaz et al, 2010). Although documenting somewhat distinct depositional environments (freshwater-dominated in the Ucayali basin; marine/tidal-dominated in the Huallaga basin), both units are laterally equivalent.…”
Section: Paleontological Contentsupporting
confidence: 79%
See 2 more Smart Citations
“…These levels can be correlated with those of the Cruzeiro Formation in the upper Yuruá ("red beds" at the Peru/Brazil border; Oppenheim, 1937). The inferred time span also coincides with that documented by the NPFB for the Pozo Fm using low-temperature thermochronology (Hermoza et al, 2005;Roddaz et al, 2010). Although documenting somewhat distinct depositional environments (freshwater-dominated in the Ucayali basin; marine/tidal-dominated in the Huallaga basin), both units are laterally equivalent.…”
Section: Paleontological Contentsupporting
confidence: 79%
“…The Chambira Fm. is also recognized in the NPFB and SPFB (e.g., Roddaz et al, 2010). Based on observations in the NPFB, Marocco et al (1996) proposed that the deposits of the Chambira Fm.…”
Section: Paleontological Contentmentioning
confidence: 97%
See 1 more Smart Citation
“…Miocene and the formation of the current Amazon River's drainage 2-Island model by recurrent Miocene marine introgressions caused by fluctuations of world sea-level and the appearance of internal Amazonian lakes 3-Appearance of geological arches, which changed the geomorphology of the Amazonian basin 1- [113,120,121,234] 2- [163] 3- [3,12,111,133,170] Riverine Barrier hypothesis, RBH The largest rivers of the Amazonian Basin formed in the late Miocene as a barrier to the dispersion of organisms [235,236] Recent lagoon hypothesis, RLH…”
Section: -Uplift Of the Northern Andes In The Latementioning
confidence: 99%
“…The most important ones are the Stability-time Hypothesis (STH), Paleogeography Hypothesis (PH), Riverine Barrier Hypothesis (RBH), Recent Lagoon Hypothesis (RLH), Refugia Hypothesis (RH), River Refuge Hypothesis (RRH), Canopy-density Hypothesis (CDH), Disturbance-Vicariance Hypothesis (DVH), Museum Hypothesis (MH), Gradient Hypothesis (GH), and Hydrogeological Recent Change Hypothesis (HRCH) (all hypotheses are explained in Table 1). Excellent reviews on the question can be found in the literature [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%